Expedited Procedures in International Commercial Arbitration Swiss and International Perspectives - Wehowsky, Andreas (sui generis Verlag, 2023)
International arbitration has enjoyed remarkable success. However, in recent years repeated concerns relating to the efficiency of the proceedings have emerged. These concerns have led to the introduction of provisions for expedited arbitral procedures. Through analysing various arbitration rules, this book will examine the require-ments under which expedited procedures are admissible, what the central char-acteristics of such procedures are, and how such procedures can be classified and described in comparison to a conventional arbitral procedure. A significant part will examine the tension between procedural efficiency on the one hand and on quality of the procedure and award on the other. In an excursus, early determination procedures will be examined to complete the tool box to increase procedural efficiency.